1982
DOI: 10.1128/iai.37.2.826-829.1982
|View full text |Cite
|
Sign up to set email alerts
|

Strain-related differences in lysozyme sensitivity and extent of O-acetylation of gonococcal peptidoglycan

Abstract: Peptidoglycan from Neisseria gonorrhoeae RD5 was completely degraded by hen egg white lysozyme and was not extensively O-acetylated. In contrast, peptidoglycans from gonococcal strains FA19 and FA102 (a penicillin-resistant mutant derived from FA19), were markedly resistant to digestion by hen egg white lysozyme and were extensively O-acetylated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 15 publications
1
46
0
Order By: Relevance
“…Rheumatoid arthritis, an autoimmune disease, is induced in animal models by undigestible high-molecularweight peptidoglycan fragments (Hamerman, 1966;Ginsburg & Sela, 1976;Chedid et al, 1978;Fox et al, 1982;Esser et al, 1985;Koga et al, 1985;Fleming et al, 1986;Stimpson et al, 1986). Indeed, in vivo studies demonstrated that the persistence of peptidoglycan in a host is directly attributable to the high degree of O-acetylation (Blundell et al, 1980;Rosenthal et al, 1982;Swim et al, 1983;Fleming et al, 1986). As in the case of deacetylation, O-acetylation could have an effect on the recognition of peptidoglycan fragments by host factors such as peptidoglycan recognition proteins.…”
Section: Biological Roles Of Peptidoglycan O -Acetylationmentioning
confidence: 99%
“…Rheumatoid arthritis, an autoimmune disease, is induced in animal models by undigestible high-molecularweight peptidoglycan fragments (Hamerman, 1966;Ginsburg & Sela, 1976;Chedid et al, 1978;Fox et al, 1982;Esser et al, 1985;Koga et al, 1985;Fleming et al, 1986;Stimpson et al, 1986). Indeed, in vivo studies demonstrated that the persistence of peptidoglycan in a host is directly attributable to the high degree of O-acetylation (Blundell et al, 1980;Rosenthal et al, 1982;Swim et al, 1983;Fleming et al, 1986). As in the case of deacetylation, O-acetylation could have an effect on the recognition of peptidoglycan fragments by host factors such as peptidoglycan recognition proteins.…”
Section: Biological Roles Of Peptidoglycan O -Acetylationmentioning
confidence: 99%
“…1) there was no evidene that either the mono-or the di-O-acetylated dimer was the better substrate. Enzyme from strain RD 5, known to have poorly O-acetylated peptidoglycan [3,4] produced almost identical results (not shown). Our previous work [7] showed that 20% of the endopeptidase activity of ether-treated gonococci was resistant to beta-lactam antibiotics.…”
Section: Resultsmentioning
confidence: 79%
“…The peptidoglycan of N. gonorrhoeae is Oacetylated [|] on about 40-50% of the available muramic acid residues [2][3][4], although strain RD 5 has greatly decreased levels of O-acetylation [3,4]. In growing cells, 65% of the total O-acetylation takes 10 rain, the remainder taking a further 50 min [5].…”
Section: Introductionmentioning
confidence: 99%
“…Both the composition of peptidoglycan itself and of associated polysaccharide affect the inflammatory properties of streptococcal cell walls. Extensive O-acetylation of the glycan backbone of PG decreases the susceptibility of peptidoglycan to lysozyme ( Gallis et al 1976, Rosenthal et al 1982. Extensive N-acetylation has the opposite effect (Amano et al 1980).…”
Section: Elimination and Degradation Of Bacterial Debrismentioning
confidence: 99%